2018
DOI: 10.1111/hae.13540
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in clinical outcomes and replacement factor VIII use in patients with haemophilia A after factor VIII pharmacokinetic‐guided prophylaxis based on Bayesian models with myPKFiT®

Abstract: Our results suggest that PK-guided prophylaxis using myPKFiT improved clinical outcomes and optimized FVIII consumption in the study population. This personalized approach may reduce bleeding rates without significantly increasing the overall cost of FVIII therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
4
32
0
Order By: Relevance
“…14,16,22,23 PK studies of non-Chinese populations have also been conducted. 24,25 A PK study of Kogenate FS ® in Canada revealed that the mean t 1/2 , CL, and was nearly identical to ours (10.18 h), whereas the CL was lower than in the present study; this discrepancy may be related to inter-individual variability, age difference, and ethnicity-related differences. 25,26 Further research is needed to compare PK among populations.…”
Section: Discussionsupporting
confidence: 73%
“…14,16,22,23 PK studies of non-Chinese populations have also been conducted. 24,25 A PK study of Kogenate FS ® in Canada revealed that the mean t 1/2 , CL, and was nearly identical to ours (10.18 h), whereas the CL was lower than in the present study; this discrepancy may be related to inter-individual variability, age difference, and ethnicity-related differences. 25,26 Further research is needed to compare PK among populations.…”
Section: Discussionsupporting
confidence: 73%
“…A number of recent reports have documented the potential benefits of individualized prophylaxis regimens based on measured PK profiles of subjects with hemophilia A. 7,[21][22][23] A challenge to the implementation of PK directed prophylaxis regimens in the past was that traditional PK studies in individuals with hemophilia were demanding as they required a long washout to achieve trough levels below the limit of quantitation of FVIII using conventional one-stage or chromogenic FVIII:C assays, followed by multiple post-infusion blood samples. Consequently, such PK studies were impractical from a clinical perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors have provided recommendations for performing the switch between different FVIII products, 6 including extended half-life FVIII (EHL). In our centre, we use extensively PopPK resources to tailor therapy, and consequently, it was also used to assess PK with rFVIII-FS, and therefore, with BAY 81-8973.…”
Section: Cross-sectional Comparative Study Of Pharmacokinetics and Efmentioning
confidence: 99%